Anger Traits Associated With Cardiovascular Risk Biomarkers in the Metabolic Syndrome. Issue 4 (July 2016) - Lemche, Alexandra V.; Chaban, Oleg S.; Lemche, Erwin
Abstract : Background: Recent studies have shown that different personality traits contribute to mortality in different subtypes of cardiovascular disease (CVD). Anger traits have been shown to promote the constellation of the metabolic syndrome (MetS), which in turn increases CVD risks. Objective: To determine covariation of anger traits with CVD biomarkers, we examined patients (N = 101; 34 men and 67 women; age, 45.6 ± 13.96 years) in a nationally sampled treatment cohort for MetS in the Ukrainian governmental healthcare system. Methods: Data collection was conducted in 2007. Laboratory data of single components of the MetS according to International Diabetes Federation Consensus were dependent measures in regression models with self-reported overt aggressivity and covert hostility in the Buss-Durkee Hostility Inventory and sociodemographic data. Structural equation models (SEMs) were tested. Results: The SEM results are in favor of a sex-adjusted 2-factor solution R 2 = 0.723), as indicated by equation-level Bentler-Raykov goodness-of-fit coefficients of 0.81 to 0.97 for paths to biological variables. Two latent components, 1 relating to aggressivity and the other to hostility, combine lipid/obesity-related measures and cholesterol-related measures, respectively. Conclusions: The SEM results suggest that CVD-risk biomarker variables in this MetS sample ( a ) associate into 2 distinct profiles and ( b ) that 1 profile associates with overt anger, whereas the other associates with covert hostility. These results could contribute to more personalized prevention and care in CVD patients.